THE EFFECT OF THE LEARNING STRATEGY AND SELF CONCEPT AGAINST THE KNOWLEDGE ABOUT OF RECYCLE WASTE EXPERIMENT IN SMA 4 KOTA TERNATE - Nurida Wahab (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2016)
The objective of this research was to know The Effect of the Learning Strategy and Self Concept against the Knowledge about of Recycle Waste in SMAN 4 Ternate. This research applied true experimental design with posttest-only control design. This population of this research is all students of class X SMAN 4 Ternate on academic year 2012/2013. The samples of this research were class X1 as experimental (PBL) and class X3 as control (Expository). The instrument of this this research namely knowledge about recycle waste test and self-concept scale questionnaire. The research data are quantitative data consisted by score knowledge about recycle waste and self-concept scale questionnaire, collected on February until April 2013. Data were analyzed by linear variant statistical analysis (ANAVA), continued with Tukey test. The result of research indicated that there were PBL toward the knowledge about recycle waste. Student with PBL having the value of knowledge higher 8, 71 % from expository of strategy. Based on this research, the researcher suggest to the teacher that this strategy can be implemented in education living environment learning.